2014
DOI: 10.7840/kics.2014.39c.4.362
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability Discovery Method Based on Control Protocol Fuzzing for a Railway SCADA System

Abstract: Key Words : Fuzzing, DNP3, Vulnerability Assessment, Control System Security, SCADA Security ABSTRACT A railway SCADA system is a control systems that provide the trains with the electricity. A railway SCADA system sends commands to the RTUs(remote terminal unit) and then it gathers status information of the field devices in the RTUs or controls field devices connected with the RTUs . The RTU can controls input output modules directly, gathers the status information of the field devices connected with it, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…At present, the commonly used vulnerability mining techniques are divided into static analysis, dynamic analysis, binary comparison, fuzzy testing, and so on [6][7][8][9][10][11][12]. Fuzzy testing has the advantages of high automation, low system consumption, low false-alarm rate, and being independent of the source code of the object program [7].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the commonly used vulnerability mining techniques are divided into static analysis, dynamic analysis, binary comparison, fuzzy testing, and so on [6][7][8][9][10][11][12]. Fuzzy testing has the advantages of high automation, low system consumption, low false-alarm rate, and being independent of the source code of the object program [7].…”
Section: Introductionmentioning
confidence: 99%
“…Fuzzing is used in dynamic stage and has two methods in which the data is entered: randomly and orderly. When choosing the data in regards to the software, it is suggested that the data is chosen by considering the characteristics of the related field and the usage of the software as well as the process [5].…”
Section: Related Workmentioning
confidence: 99%